2016
DOI: 10.1002/2016jd025043
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous diurnal variation of atmospheric potential gradient and air‐Earth current density observed at Maitri, Antarctica

Abstract: The scope of this paper is to explore the mechanisms operating over Maitri (70.76°S, 11.74°E, 117 m above mean sea level), a coastal Antarctic station, that produce an anomalous fair‐weather diurnal pattern of the atmospheric electric potential gradient (PG) and air‐Earth current density (AEC). The anomaly in the diurnal variations of AEC and the PG is displaying an ostensible minimum at ~10 UT and a diminished response to the thunderstorm over the African continent in the 14–16 UT time frame. The data sets (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…Identifying suitable PG or AEC density data for the investigation of the global feature is usually done by applying some rejection criterion which is based on the visual observation of the sky condition (i.e., visibility), and the limiting threshold for wind speed, etc., (Deshpande & Kamra, 2001; Minamoto & Kadokura, 2011; Ruhnke, 1962). The global features are well represented/detected in the PG and AEC density variations in Antarctic Plateau (Bering et al., 1991; Burns et al., 1995, 2017; Byrne et al., 1993; Cobb, 1977; Frank‐Kamenetsky et al., 2001; Jeeva et al., 2016). However, these variations also show strong signatures of local electrical disturbances in coastal Antarctica (Burns et al., 1995; Jeeva et al., 2016; Minamoto & Kadokura, 2011).…”
Section: Observations and Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Identifying suitable PG or AEC density data for the investigation of the global feature is usually done by applying some rejection criterion which is based on the visual observation of the sky condition (i.e., visibility), and the limiting threshold for wind speed, etc., (Deshpande & Kamra, 2001; Minamoto & Kadokura, 2011; Ruhnke, 1962). The global features are well represented/detected in the PG and AEC density variations in Antarctic Plateau (Bering et al., 1991; Burns et al., 1995, 2017; Byrne et al., 1993; Cobb, 1977; Frank‐Kamenetsky et al., 2001; Jeeva et al., 2016). However, these variations also show strong signatures of local electrical disturbances in coastal Antarctica (Burns et al., 1995; Jeeva et al., 2016; Minamoto & Kadokura, 2011).…”
Section: Observations and Resultsmentioning
confidence: 96%
“…As an example, Jeeva et al. (2016) carried out the GEC experiments at Maitri for about 6 years spread during 2006–2020. The lead author found that the strong winds associated with the snow particles, snowfall, and drifting snow caused severe fluctuation in the PG and AEC density variations, during his stay in Antarctica.…”
Section: Observations and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Burns et al (2012) found global signatures in the daily and seasonal variation in PG at Vostok when meteorological disturbances related to temperature and wind speed effects were removed. Furthermore, PG measurements were performed at Maitri station (70.76°S, 11.74°E), reported by Jeeva et al (2016), who found that local katabatic winds could also produce substantial local effects on PG.…”
Section: Introductionmentioning
confidence: 99%